Desain e-Modul Fisika Sebagai Pembelajaran Berbasis Masalah dalam Meningkatkan Hasil Belajar Siswa - Andriani, Welli; Sundari, Putri Dwi; Dwiridal, Letmi; Dewi, Wahyuni Satria; Fortuna, Aprilla (Universitas Negeri Padang, 2024)
Physics learning is learning that cannot be separated from mathematical learning, so students tend to get bored more easily if the teaching materials and learning models used are not appropriate, thus causing low student motivation to learn and resulting in low student learning outcomes. In solving this problem, there is a need for technological developments, learning tools are increasingly referring to digitalization, such as the teaching materials used are starting to be digital-based so that they are more interactive, such as the use of e-modules, which can contain pictures, animations, audio and video learning, so that students are more interested. for learning, apart from teaching materials, learning models also support the achievement of learning objectives, learning models that can be used so that students are active in the learning process are problem-based learning. The aim of this research is to produce a problem-based learning e-module design to improve student learning outcomes. This research includes development research. The development model used is a prototype model, namely the first stage listen to customers, the second stage is build/revise mock-up (design and the next stage is customer test driver mock-up (evaluation). This e-module is designed with the Canva application to design the cover and module display and flipbook hyzine help to make the module display more interactive.